Mengungkap Dimensi Shalat dalam Kehidupan Spiritual dan Sosial: Kajian Tematik Ayat-Ayat Shalat dengan Pendekatan Psikologi Perspektif Muhammad Bahnasi - Burniat, Burniat; Sassi , Komarudin (Green Publisher Indonesia, 2025)
This study examines the thematic verses of prayer through an integration-interconnection paradigm with Muhammad Bahnasi's psychological perspective. Prayer, as an act of worship, has dimensions that go beyond being just a religious obligation. The purpose of this study is to reveal the dimensions of prayer that relate not only to spiritual aspects but also to social ones, as well as how prayer can shape a person to be pious both spiritually and socially. The method used in this study is a literature review with thematic analysis of prayer-related verses in the Qur'an, connecting them to Muhammad Bahnasi's psychological perspective to explore the psychological values contained in the practice of prayer. The findings show that prayer is not just a religious obligation but also a universal human need. Prayer contains dimensions of discipline (an-Nisa: 103), concentration, intellectual intelligence, emotional stability, as well as physical health (al-Maidah: 6) and spiritual well-being (al-Baqarah: 45). Prayer also fosters social righteousness, which is essential for building integrity in social and national life, creating unity, harmony (an-Nisa: 102), collective responsibility (al-‘Asr: 3), and social change (al-‘Ankabut: 45). These dimensions can be formulated into a concept that shapes a person with positive character, both spiritually and socially. This study enriches the understanding of prayer as worship that benefits the individual spiritually while also promoting social well-being, which can be applied to create peace and harmony in society.